2005
DOI: 10.1016/j.devcel.2004.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Msx1 and Pax3 Cooperate to Mediate FGF8 and WNT Signals during Xenopus Neural Crest Induction

Abstract: FGF, WNT, and BMP signaling promote neural crest formation at the neural plate boundary in vertebrate embryos. To understand how these signals are integrated, we have analyzed the role of the transcription factors Msx1 and Pax3. Using a combination of overexpression and morpholino-mediated knockdown strategies in Xenopus, we show that Msx1 and Pax3 are both required for neural crest formation, display overlapping but nonidentical activities, and that Pax3 acts downstream of Msx1. In neuralized ectoderm, Msx1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
391
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(417 citation statements)
references
References 48 publications
22
391
4
Order By: Relevance
“…Furthermore, AP2γ has redundant activities with AP2α in neural crest induction and nonneural ectoderm derivative development [26]. Other factors such as Pax7, Msx1, Zic1, Dlx5 and AP2α were shown as neural border specifiers [30,[63][64][65][66][67][68]. During early neuralization of the chick embryo, some factors are mainly expressed in the peripheral (Pax7, Dlx5 and AP2α) or caudal (Msx1) ectoderm and the expressions of others (Zic1) partially overlaps with cSox2 expression [68].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AP2γ has redundant activities with AP2α in neural crest induction and nonneural ectoderm derivative development [26]. Other factors such as Pax7, Msx1, Zic1, Dlx5 and AP2α were shown as neural border specifiers [30,[63][64][65][66][67][68]. During early neuralization of the chick embryo, some factors are mainly expressed in the peripheral (Pax7, Dlx5 and AP2α) or caudal (Msx1) ectoderm and the expressions of others (Zic1) partially overlaps with cSox2 expression [68].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have indicated that Wnts are neural crest inducers (reviewed by Raible, 2006). It was reported that the cooperative function of Pax3 and Zic1, in concert with Wnt signaling, is essential for neural crest specification (Monsoro-Burq et al, 2005;Sato et al, 2005). The transcription factor Xsnail, which is expressed as early as Xhairy2 in the prospective neural crest, is known to have the ability to induce neural crest marker genes (Aybar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…17 In chick as well as in Xenopus and zebrafish, NPB markers are expressed at mid-to late gastrula stages. 10,18,19 A sharp and defined NPB is observed in chick embryos during and after neurulation, 10,20 and it appears that the competence to form NC is retained longer, well into neurula stages, in chick ectoderm as compared to the frog. 7,21,22 This discrepancy is likely due to the timing of gastrulation and neurulation in amphibian and chick embryos.…”
Section: When Is the Npb Specified?mentioning
confidence: 94%
“…30,39 BMP and Wnt/b-Catenin signaling functionally interact with Pax3, Zic1 and Ap2a in later phases to induce bona fide NC fate. 19,30,40,41 Likewise, Wnt/b-Catenin signaling is essential for NPB specification in epiblast explants from chick blastulae, where Wnt activity precedes and upregulates bmp4, 17 as well as for expression of NPB genes in hESCs. 11 Steventon and colleagues have analyzed Wnt/ b-Catenin activity in Xenopus embryos using the TOPFlash reporter gene assay.…”
Section: Wnt Signalingmentioning
confidence: 99%
See 1 more Smart Citation